Comparative categorization method: Using 2-AFC strategy in constant-reference duo-trio for discrimination of multiple stimuli from a reference. (December 2017) - Jeong, Yu-Na; van Hout, Danielle; Groeneschild, Chantalle; Lee, Hye-Seong
Highlights: Methodology was developed for sensory panels to use the unspecified 2-AFC. It included a familiarization for a difference and constant-reference duo-trio tests. Its performance was compared with traditional duo-trio and unspecified tetrad. It was called comparative classification and use of 2-AFC strategy was confirmed. It was more reliable than other unspecified methods for testing multiple pair stimuli. Abstract: In the fast moving consumer goods industry, unspecified (overall) sensory difference tests are commonly used with sensory panels to compare multiple types of stimuli against a gold standard. In order to measure sensory differences accurately and reliably, it is important to investigate the efficiency of unspecified sensory difference test methods not only in terms of statistical test power, but also in practice, i.e., operational test power. One unspecified difference test method, the duo-trio method using constant-reference, is procedurally equivalent to the 2-AFC with reminder (2-AFCR), for which the 2-AFC decision strategies can be used by performing a comparative categorization task. However, the feasibility and efficiency of the comparative categorization task using a constant-reference duo-trio method has not been tested for the discrimination of multiple stimuli from a reference. The objectives of the present study were 1) to evaluate the adoption of the 2-AFC decision strategy in such comparative categorization methods for discriminating multiple products from a reference, and 2) to compare the efficiency and power of these comparative categorization methods with the unspecified tetrad and balanced-reference duo-trio methods. Using two sensory panels to discriminate two different iced tea stimuli from a reference, our results confirmed that a 2-AFC strategy can be adopted in comparative categorization methods without specifying sensory attributes. With an equal number of tastings, the comparative categorization methods using a 2-AFC strategy showed comparable operational test power with the unspecified tetrad method. Among the two versions (using a constant-reference duo-trio with the reference at the first position (DTF) and duo-trio with a reference presented first and in the middle of two alternative stimuli (DTFM)) of the comparative categorization methods examined in the present study, DTF was more reliable across repeated sessions than other unspecified methods investigated.